4(v-1)=-9v+9

Simple and best practice solution for 4(v-1)=-9v+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(v-1)=-9v+9 equation:


Simplifying
4(v + -1) = -9v + 9

Reorder the terms:
4(-1 + v) = -9v + 9
(-1 * 4 + v * 4) = -9v + 9
(-4 + 4v) = -9v + 9

Reorder the terms:
-4 + 4v = 9 + -9v

Solving
-4 + 4v = 9 + -9v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '9v' to each side of the equation.
-4 + 4v + 9v = 9 + -9v + 9v

Combine like terms: 4v + 9v = 13v
-4 + 13v = 9 + -9v + 9v

Combine like terms: -9v + 9v = 0
-4 + 13v = 9 + 0
-4 + 13v = 9

Add '4' to each side of the equation.
-4 + 4 + 13v = 9 + 4

Combine like terms: -4 + 4 = 0
0 + 13v = 9 + 4
13v = 9 + 4

Combine like terms: 9 + 4 = 13
13v = 13

Divide each side by '13'.
v = 1

Simplifying
v = 1

See similar equations:

| 6z-3z+5-4=3z-5+4 | | -2(d+6)-3(4d-2)=22 | | 4x-8=11y-1 | | p=5/9*350000 | | -4(x-4)=28+8x | | 2g-12=16-10h | | 13.50/3 | | -45-5+2b=10 | | 175m-75m-53625=55000-175m | | -12x-3x=-8 | | Z=6x+px+2 | | 4x-45=7(x-9) | | -(4-6n)=n+11 | | B-1/2=b/3+7 | | ((7x+6)(2x+10))/((6x+2)(7x+5)) | | y=6/7x-2 | | -7+14k-13+-(-5k)+3= | | x/-8=-1-(-3) | | 3x=3(8-7x) | | 20.5=(w/3600)(703) | | 22-8x=-5(5x-1) | | -2(-3x+3y)=-2(-27) | | 3xy+3x=6 | | (11x)/6+2/3=2x | | 80x+2250=70x+5600 | | x+19+4x=-15-4x-20 | | 15x+7+19=100 | | 3(v-2)=7v-46 | | 117=r/29-(-115) | | 125x+10=230x+7 | | -5.64(6.6+6x)=-30.17784+0.7x | | G=x^2-6x+9/2 |

Equations solver categories